PENGARUH KAPASITAS SUMBERDAYA MANUSIA, PEMANFAATAN TEKNOLOGI INFORMASI, DAN PENGENDALIAN INTERN AKUNTANSI TERHADAP NILAI INFORMASI PELAPORAN KEUANGAN PEMERINTAH DAERAH, STUDI PADA PEMERINTAH - Hendira Rita Kartika; Dewi Amalia (Universitas Ahmad Dahlan, 2014)
This research aims to understand the influence of the capacity of human resources, the utilization of information technology, internal control and accounting on the value of information reporting local government finance. Of respondents in this research is the head and staff the subsection accounting and finance at penatausahaan skpd magelang city of central java province. The number of respondents in this research is 65. Data collection done by means of spreading the questionnaire directly to the secretariat skpd magelang city. The technique of analysis of data using linear regression analysis double. The result of testing on each of the independent variable shows that the capacity of human resources have influence on the information the government financial reporting magelang the city. While the use of information technology and control of internal accounting have no influence on the information the government financial reporting Magelang city